Successor Selection in family firms: A game theory approach - Bañegil Palacios, Tomás M. (2018)
The governance challenge of management succession is critical in the family firms. This paper provides insight on the role that the emotional factors as well as the founder’s governance approach, have on successor selection in family firms. The successor selection is studied using game theory. The paper models games for both approaches of the founder towards successor selection and then compares both. The results demonstrate that the emotional factors determine the successor outcome. The founder’s governance approach is essential to ensure firm continuity as well as secure that his preferred successor is indeed appointed successor. This is one of only few studies investigating family firm succession using game theory, and the first, to the best of our knowledge, to include the emotional factors as variables in the analysis. This paper also contributes to analytically demonstrate the importance of the founder adopting an activist approach to the succession process to ensure family firm intergenerational continuity.